2023
DOI: 10.1002/rco2.80
|View full text |Cite
|
Sign up to set email alerts
|

The role of microRNAs in muscle wasting and recovery during critical illness: a systematic review

Maria Borja‐Gonzalez,
Sarah Coyne,
Sarah Fagan
et al.

Abstract: IntroductionCritical illness associated with intensive care unit (ICU) admission often results in persistent skeletal muscle wasting and may lead to frailty in older and patients with multi‐morbidity. Early recognition of patients at high‐risk of long‐term complications could provide opportunities to minimize the impact of critical illness and improve health and quality of life. MicroRNAs (miRs) are short, non‐coding RNAs that regulate approximately two‐thirds of the human genome and are involved in most biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“…A systematic review by Borja-Gonzalez et al focused on these characteristics of miRs and approached the role of miRs in muscle wasting and recovery during critical illness. 15 They examined the expression levels of miRs in muscle and circulation in the context of muscle weakness and/or frailty related to critical illness and revealed that 27 different miRs were dysregulated in muscle and 4 in blood from seven studies that met their inclusion criteria. In patients with ICU-AW, miR-424-5p and miR-542-3p/miR-542-5p levels in muscle correlated with muscle mass and strength, increased during ICU stay, and decreased 7 days after ICU discharge.…”
mentioning
confidence: 99%
“…A systematic review by Borja-Gonzalez et al focused on these characteristics of miRs and approached the role of miRs in muscle wasting and recovery during critical illness. 15 They examined the expression levels of miRs in muscle and circulation in the context of muscle weakness and/or frailty related to critical illness and revealed that 27 different miRs were dysregulated in muscle and 4 in blood from seven studies that met their inclusion criteria. In patients with ICU-AW, miR-424-5p and miR-542-3p/miR-542-5p levels in muscle correlated with muscle mass and strength, increased during ICU stay, and decreased 7 days after ICU discharge.…”
mentioning
confidence: 99%